2014
DOI: 10.1021/ja502729x
|View full text |Cite
|
Sign up to set email alerts
|

Porphodilactones as Synthetic Chlorophylls: Relative Orientation of β-Substituents on a Pyrrolic Ring Tunes NIR Absorption

Abstract: Porphodilactones represent the porphyrin analogues, in which the peripheral bonds of two pyrrole rings are replaced by lactone moieties. They provide an opportunity to investigate how β-substituent orientation of porphyrinoids modulates the electronic structures and optical properties, in a manner similar to what is observed with naturally occurring chlorophylls. In this work, a comprehensive description of the synthesis, characterization, and optical properties of meso-tetrakispentafluorophenylporphodilactone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 46 publications
11
97
0
Order By: Relevance
“…Notably, Gd‐4 showed an extinction coefficient ratio of Q y (0,0) band and Soret band ( ɛ Q(0,0) / ɛ Soret ) up to 0.56. Such redshifted absorption with increasing intensity, along with the replacement of β‐oxazolone moieties and the orientation of β‐dioxazolone moieties, is consistent with our previously reported Zn, Pt, and Pd analogs, and suggests the capability for effective excitation in the deep‐red to NIR region.…”
Section: Resultsmentioning
confidence: 91%
“…Notably, Gd‐4 showed an extinction coefficient ratio of Q y (0,0) band and Soret band ( ɛ Q(0,0) / ɛ Soret ) up to 0.56. Such redshifted absorption with increasing intensity, along with the replacement of β‐oxazolone moieties and the orientation of β‐dioxazolone moieties, is consistent with our previously reported Zn, Pt, and Pd analogs, and suggests the capability for effective excitation in the deep‐red to NIR region.…”
Section: Resultsmentioning
confidence: 91%
“…The similarity of the conformational effects of a pyrrolic β,β′‐double bond and a lactone moiety was amply demonstrated before 25c. 26b, 32b, 37…”
Section: Resultsmentioning
confidence: 98%
“…Both the spectral resemblance of the β,β′‐lactone moiety to a double bond and its bathochromic effect in chlorin‐type chromophores were observed before 25c. 26b, 32b, 38…”
Section: Resultsmentioning
confidence: 98%
“…Shen and Zhang et al. reported the synthetic porphodilactones 44 and 45 , in which two pyrrole rings of the porphyrin ligand were replaced by oxazolone moieties (Scheme ) 32. Porphodilactone isomers 40 were obtained by the reaction of porphyrin 39 or porpholatone 46 with an excess of Oxone® ( 39 : 12 eq and 46 : 4 eq), using RuCl 3 and 2,2′‐bipyridine as catalysts,33 in 45 and 53 % yield, respectively.…”
Section: Tetra‐unit Porphyrinsmentioning
confidence: 99%
“…A value of 0.87 was obtained for cis ‐porphodilactone zinc complex 42 irradiated with a 635 nm laser beam, while free‐base cis ‐porphodilactone 45 showed no singlet oxygen production at all under the same treatment. Further photocytotoxicity studies have demonstrated the potential utility of porphodilactones 41 , 42 , and 44 as NIR PDT photosensitizers 32…”
Section: Tetra‐unit Porphyrinsmentioning
confidence: 99%